Cultural Mediation and Islamic Organizations: Sundanese Identity Among Muhammadiyah, Persis, and Nahdlatul Ulama In Garut, West Java - Syi'aruddin, Mohammad Anwar; Mustapa, Hasan (Universitas Islam Negeri Raden Intan Lampung, 2026)
While numerous studies have explored tensions among Islamic organizations in Indonesia, limited attention has been given to local cultural mechanisms that foster inter-organizational cohesion. Sundanese culture is one of the cultures that spread and characterizes the citizens of West Java, Garut is one of them. Today, Garut is categorized as a cohesive area related to the existence of Islamic organizations, such as Muhammadiyah, Persis, and NU. That is, there is almost no conflict between organizations. Therefore, the researcher's hypothesis is that Sundanese culture is one of the factors that bind the Islamic organizations together, resulting in a cohesive system. This type of research is qualitative, using a sociological approach and descriptive method. This study explains that Sundanese culture is one of the factors that binds the relationship between Muhammadiyah, Persis, and NU Islamic organizations in Garut Regency. There are several forms that indicate that Sundanese culture is one of the factors that glue the three organizations together, including; first, ethics or etiquette is the most important in communicating and interacting which is applied to the rules of communication; adab to sahandapeun (younger), fellow, and saluhureun (older); second, the maintenance of village culture which indicates the importance of sauyunan that is applied through friendship; third, the use of Sundanese as the mother tongue which is brought to the level of communication both formal and non-formal so that it has implications for closeness and intimacy; fourth, continue to instill the values ​​of compassion, honing, and nurturing among them which are applied to religious learning circles (ta’lim) Keywords: Sundanese Culture; Islamic Organizations; Social Cohesion; Religious Groups